Pharmacoeconomics and Utilisation of Antidiabetic Medications among Type 2 Diabetes Mellitus Patients: A Longitudinal Study - Bikash Chandra Das; P Ansuman Abhisek; Deepak Choudhury; Suvendu Kumar Panda; Jayanti Prava Behera; Supriya Pradhan; Trupti Rekha Swain; Sasmita Mallick (Journal of Clinical and Diagnostic Research)
Introduction: Patients with Type 2 Diabetes Mellitus (T2DM) typically require long-term treatment with antidiabetic medications, resulting in a significant financial burden on both the individual and the global economy. Aim: To assess the patterns of drug utilisation and the economic aspects of antidiabetic medications in individuals with diabetes mellitus. Materials and Methods: The current study was a hospital-based longitudinal study conducted between October 2017 and September 2019. A total of 132 diagnosed cases of T2DM, aged 18 years and older, who had been on antidiabetic medications in the past three months, were included in the study. Pregnant women and patients in diabetic coma were excluded from the study. A predesigned, pretested, semistructured questionnaire was used to collect data from the patients or their legally accepted relatives. The subjects were followed-up at three and six months to determine any changes in the type and doses of medication. Laboratory parameters such as Fasting Blood Sugar (FBS) and Postprandial Blood Sugar (PPBS) were measured at baseline and at six months, along with a history of any complications of diabetes. The data were analysed using Statistical Package for the Social Sciences (SPSS) version 27.0. Results: A total of 132 patients were included, of which most patients were male (65.9%), aged 60 years or above (50.8%), illiterate (79.5%), and resided in rural areas (94.7%). The Average Cost-Effectiveness Ratio (ACER) for reducing a unit of FBS was higher compared to PPBS across all forms of the drug. The ACER at three months showed a constant increase, from 24.56 for metformin only to 2709.26 for insulin with Oral Hypoglycaemic Agents (OHA) for FBS, and from 7.83 for metformin only to 907.47 for insulin with OHA for PPBS. Metformin was the most commonly prescribed medication, both as a standalone therapy and in combination therapy. Conclusion: Present investigation showed that rational prescribing effectively reduced blood sugar readings. Metformin and Glimepiride were the predominant pharmaceuticals utilised for the treatment of diabetes. The cost-effectiveness study indicates that the financial burden of diabetes is substantial, particularly when considering the socio-economic status of individuals.